1982
DOI: 10.1002/srin.198205408
|View full text |Cite
|
Sign up to set email alerts
|

Development of texture in low carbon Al‐killed sheet steels after uniaxial tensile deformation, deep drawing and stretching

Abstract: Investigations of texture changes in aluminium‐killed low‐carbon unalloyed sheet steels by means of neutron diffraction during uniaxial tensile deformation, deep drawing and biaxial stretching. Calculation of the R‐values. Application for the prediction of unfavourable deformation data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The orientation distribution function (ODF) is then used as a weighting factor in the prediction of the plastic property of interest. Such theoretical predictions lead to reasonably good agreement with the experimental plastic strain ratio, for example Bunge [2], Szpunar [3], and Semiatin et al [4]; although Dabrowski et al [5] observed fairly large discrepancies in an aluminium-killed steel.…”
Section: Introductionmentioning
confidence: 71%
“…The orientation distribution function (ODF) is then used as a weighting factor in the prediction of the plastic property of interest. Such theoretical predictions lead to reasonably good agreement with the experimental plastic strain ratio, for example Bunge [2], Szpunar [3], and Semiatin et al [4]; although Dabrowski et al [5] observed fairly large discrepancies in an aluminium-killed steel.…”
Section: Introductionmentioning
confidence: 71%